DIFERENSIASI PRODUK, MANAJEMEN KERELASIAN PELANGGAN, DAN PENETAPAN HARGA DALAM KINERJA PEMASARAN - Joni Tesmanto; Natalia Titik Wiyani (Panca Sakti Bekasi : Jurnal Pendidikan dan Bisnis, 2019)
The problem studied in this research dealt with the implementation of product differentiation, customer relationship management, price fixing and their effect on customer values implying on marketing performance. Marketing performance can be implemented from the creation of superior customer values. Batik customers will provide higher contribution to the Small, Micro Enterprise which is considered to give the best customer value for itself. High marketing performance has great potential in obtaining loyal customers